2021
DOI: 10.1002/jev2.12072
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial ischemia‐reperfusion induced cardiac extracellular vesicles harbour proinflammatory features and aggravate heart injury

Abstract: Extracellular vesicles (EVs) curb important biological functions. We previously disclosed that ischemia‐reperfusion (IR) induces increased release of EVs (IR‐EVs) in the heart. However, the role of IR‐EVs in IR pathological process remains poorly understood. Here we found that adoptive transfer of IR‐EVs aggravated IR induced heart injury, and EV inhibition by GW4869 reduced the IR injury. Our in vivo and in vitro investigations substantiated that IR‐EVs facilitated M1‐like polarization of macrophages with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 61 publications
(68 reference statements)
3
76
0
Order By: Relevance
“…More importantly, exosomes released from these ATM‐inhibited hypoxic CAFs (Hyp‐CAF Ku‐Exo, Hyp‐CAF shATM‐Exo) decreased tumour cell invasive ability by 47.7%–50.8% compared with corresponding controls (Hyp‐CAF DMSO‐Exo, Hyp‐CAF shNC‐Exo, P < 0.01) (Figure S2D‐S2E , 12th vs. 10th, and 16th vs. 14th image/histogram on the right), suggesting that oxidized ATM in CAFs can promote tumour cell invasion mainly via exosome release. In addition, pharmacologically blocking exosome release from hypoxic CAFs (Figure S2F ) by GW4869, a non‐competitive N‐SMase inhibitor (Ge et al., 2021 ) with non‐detectable effect on the viability of CAFs (Figure S2G ), reduced the effect of Nor‐CAF‐CM on tumour cell invasion compared with Nor‐NF‐CM (Figure S2H‐S2I , 1st vs. 2nd or 3rd, 2nd or 3rd vs. 4th image/histogram on the left). Especially, the reduced effect of hypoxic CAFs‐derived CM caused by GW4869 treatment (Hyp‐CAF‐GW‐CM) on tumour cell invasion was more obvious compared with its control CM (Hyp‐CAF‐DMSO‐CM or Hyp‐CAF‐CM) (Figure S2H‐S2I , 5th or 6th vs. 7th image/histogram on the right).…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, exosomes released from these ATM‐inhibited hypoxic CAFs (Hyp‐CAF Ku‐Exo, Hyp‐CAF shATM‐Exo) decreased tumour cell invasive ability by 47.7%–50.8% compared with corresponding controls (Hyp‐CAF DMSO‐Exo, Hyp‐CAF shNC‐Exo, P < 0.01) (Figure S2D‐S2E , 12th vs. 10th, and 16th vs. 14th image/histogram on the right), suggesting that oxidized ATM in CAFs can promote tumour cell invasion mainly via exosome release. In addition, pharmacologically blocking exosome release from hypoxic CAFs (Figure S2F ) by GW4869, a non‐competitive N‐SMase inhibitor (Ge et al., 2021 ) with non‐detectable effect on the viability of CAFs (Figure S2G ), reduced the effect of Nor‐CAF‐CM on tumour cell invasion compared with Nor‐NF‐CM (Figure S2H‐S2I , 1st vs. 2nd or 3rd, 2nd or 3rd vs. 4th image/histogram on the left). Especially, the reduced effect of hypoxic CAFs‐derived CM caused by GW4869 treatment (Hyp‐CAF‐GW‐CM) on tumour cell invasion was more obvious compared with its control CM (Hyp‐CAF‐DMSO‐CM or Hyp‐CAF‐CM) (Figure S2H‐S2I , 5th or 6th vs. 7th image/histogram on the right).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we studied whether leukemic cell-derived sEVs play roles in affecting CD8+ T cell function. GW4869, an inhibitor of sEV secretion (Ge et al, 2021), decreased sEV secretion from leukemic cells (Figure S3C) and showed almost no effect on leukemic cell and CD8+ T cell viability (Figure S3D). Interestingly, blocking sEV secretion by leukemic cells with GW4869 rescued CD8+ T cell proliferation (Figures 2a and S4A), IL-2 and IFN-γ secretion (Figures 2b,c and S4B,C), CD25 expression (Figures 2d and S4D), and granzyme B production (Figures 2e and S4E).…”
Section:  Leukemic Cells Impair the Immune Function Of Cd+ T Cells Via Sev Releasementioning
confidence: 99%
“…Increases cardiomyocyte apoptosis in vitro via the downregulation of HIF-1α, RNA-binding protein Quaking, and SIRT1 [153,154,198], enhances the inflammatory response through the activation of the JAK2/STAT1 pathway [155], increases ROS generation during IRI [199].…”
Section: Mir-155mentioning
confidence: 99%